A case report on the safety and efficacy of aripiprazole for depression in Brugada syndrome - Monica Fahmy, PharmD; Youssef Bessada, PharmD; Cassandra Ramsey, APRN; Jennifer R. Zigun, MD (Mental Health Clinician)
Clozapine is the only medication approved for treatment-resistant schizophrenia. Clozapine toxicity associated with COVID-19 infection could be amplified by concomitant nirmatrelvir/ritonavir. Knowledge gaps among clinicians and patients led to patient safety concerns and the implementation of a quality improvement (QI) project focused on rapid education dissemination. This QI project focused on clinicians, patients, and caregivers. Steps included clinician education at system, regional, and national levels and patient/caregiver education at system and regional levels. Optimization of electronic health record (EHR) tools facilitated efficient clinical workflows, targeted patient education to facilitate shared decision making, and promoted best practices. Education concerning risk for COVID-19, clozapine toxicity, and nirmatrelvir/ritonavir drug interactions was distributed to more than 1400 clinicians via e-mail and conference presentations. Enduring continuing education materials had more than 1200 views. Verbal or written education was rapidly delivered to 231 patients/caregivers and documented via autotext, an EHR tool. Following presentation of this QI project at a schizophrenia conference, more than 95% of attendees, including health care clinicians and patients/caregivers, rated their understanding of COVID-19, clozapine toxicity, and the interaction with nirmatrelvir/ritonavir as “very high” or “high.” Separately, web-hosted continuing education platforms indicated that more than 75% of clinicians rated their understanding of these 2 issues as “very high” or “high” upon module completion. By educating patients/caregivers and clinicians about COVID-19 infection and nirmatrelvir-/ritonavir-associated toxicity risks, this project helped ensure safe prescription of clozapine during the COVID-19 pandemic. This project could serve as a rapid risk mitigation dissemination model of patient safety education.